2001
DOI: 10.1086/323571
|View full text |Cite
|
Sign up to set email alerts
|

The Orbit of the Massive X-Ray Binary LS 5039

Abstract: We present the first spectroscopic orbit for the massive X-ray binary LS 5039, which we find to be a shortperiod ( days) and highly eccentric ( ) system. The low-mass function for P p 4.117 ‫ע‬ 0.011 e p 0.41 ‫ע‬ 0.05 the orbit appears to be most consistent with a neutron star companion, although a black hole remains a possibility if the system has a low inclination. The spectrum of the O7 V optical star appears to be normal for its type (suggesting that there is little flux in the red from an accretion disk) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 14 publications
8
55
0
Order By: Relevance
“…It is important to establish the reliability of the EOT method at these low flux levels. For example, detection of the black hole candidate LS 5039 (McSwain et al 2001) in the low-energy gamma-ray band has not been reported previously in the literature, and 4U 1812À12 was reported only for the first time in Barret et al (2003).…”
Section: Consistency Of Deep Sample Detectionsmentioning
confidence: 95%
“…It is important to establish the reliability of the EOT method at these low flux levels. For example, detection of the black hole candidate LS 5039 (McSwain et al 2001) in the low-energy gamma-ray band has not been reported previously in the literature, and 4U 1812À12 was reported only for the first time in Barret et al (2003).…”
Section: Consistency Of Deep Sample Detectionsmentioning
confidence: 95%
“…This high eccentricity probably results from the huge mass loss that occurred with the supernova (SN) explosion that gave birth to the compact star in the system (Bhattacharya & van den Heuvel 1991;Nelemans, Tauris, & van den Heuvel 1999). Binaries that suffer large mass loss in a SN are expected to become runaway stars, and recently both we (McSwain et al 2001b) and Ribó et al (2002) found that LS 5039 has a relatively large proper motion that indicates that the binary has a record-breaking peculiar space velocity among MXRBs.…”
Section: Introduction Ls 5039 Is a Relatively Faint (mentioning
confidence: 89%
“…Some kind of close interaction must have occurred because by the time of the SN the mass ratio had reversed and the separation had increased (Wellstein, Langer, & Braun 2001). Given this evidence of a pre-SN interaction, the observed C deficiency of the primary (McSwain et al 2001a) probably results from nuclear-processed gas transferred from the SN progenitor. The currently faster than synchronous rotation of the primary (McSwain et al 2001a) may correspond to the synchronous rate in the shorter period, pre-SN configuration.…”
Section: X-ray Fueling By Wind Accretionmentioning
confidence: 99%
See 2 more Smart Citations